2000
DOI: 10.1099/0022-1317-49-11-993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of genomic differences unique to Burkholderia pseudomallei by comparison with B. thailandensis

Abstract: Melioidosis is an infectious disease caused by Burkholderia pseudomallei. Genomic subtractive hybridisation was performed with the closely related avirulent species B. thailandensis to identify virulence genes of B. pseudomallei. The subtractive hybridisation products were highly speci®c for B. pseudomallei. Sequence analysis revealed a number of putative virulence factors, as well as apparently novel sequences of unknown function. The subtracted library contained DNA regions of relatively low G C mol% content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Manzeniuk et al found that 92% of B. pseudomallei strains produced temperate bacteriophages, demonstrating that prophages are relatively common in this bacterial species (45). Brown and Beacham performed subtractive hybridization between B. pseudomallei and B. thailandensis and identified multiple B. pseudomallei-specific mobile genetic elements, including a P2-like prophage (9). Taken together, the results demonstrate that there is considerable diversity in the mobile genetic elements that B. pseudomallei strains harbor.…”
Section: Discussionmentioning
confidence: 64%
“…Manzeniuk et al found that 92% of B. pseudomallei strains produced temperate bacteriophages, demonstrating that prophages are relatively common in this bacterial species (45). Brown and Beacham performed subtractive hybridization between B. pseudomallei and B. thailandensis and identified multiple B. pseudomallei-specific mobile genetic elements, including a P2-like prophage (9). Taken together, the results demonstrate that there is considerable diversity in the mobile genetic elements that B. pseudomallei strains harbor.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, subtractive hybridisation analysis between B. pseudomallei strain 08 and Burkholderia thailandensis, a nonpathogenic relative of B. pseudomallei, indicates that GIs are key determinants of genome plasticity (28). Of 92 sequence fragments found to be present in B. pseudomallei strain 08 and absent from B. thailandensis, only 53 (58%) can be mapped to the K96243 genome.…”
Section: Resultsmentioning
confidence: 99%
“…Although important genomic differences exist between the two closely related species B. pseudomallei and B. thailandensis, the genomes of these two species are regarded to be broadly similar (Brown and Beacham, 2000;Yu et al, 2006). Because of this extensive genomic similarity between B. pseudomallei and B. thailandensis, it has been suggested that B. thailandensis could be used as a possible model system for studying certain aspects of B. pseudomallei behaviour (Yu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%